How Effective is Implementing Jigsaw IV in Teaching Reading of the Narrative Text to the Eleventh Grade Students? - Lalu Jaswadi Putera; Udin Udin (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study aims at investigating the effectiveness of implememting Jigsaw IV technque in teaching raeding of the narrtive text to the 11th grade students at SMAN 1 Kuripan West Lombok Regency. The current study involved the eleventh grade students as the samples of the study. It applied a two-group of pre-test and post-test design with the total of 24 students in the Experimental Group and 24 students in the Controlled Group. Upon the comletion of the pre-test and prior to the post-test, some treatments in the form of teaching and learning reading of narrative text using Jigsaw IV technique were given to the Experimental Group. The results show that after implementing the Jigsaw IV technique in teaching reading using narrative text, the students' reading comprehension achievement increased significantly with a substantial level of effectiveness. It indicates through the findings that using Jigsaw IV technique in teaching reading of the narrative text helps students improve their reading comprehension.